Cognitive-Behavior Therapy for Low Self-Esteem: A Case Example - McManus, F; Waite, P; Shafran, R (2009)
Low self-esteem is a common, disabling, and distressing problem that has been shown to be involved in the etiology and maintenance of a range of Axis I disorders. Hence, it is a priority to develop effective treatments for low self-esteem. A cognitive-behavioral conceptualization of low self-esteem has been proposed and a cognitive-behavioral treatment (CBT) program described (Fennell, 1997, 1999). As yet there has been no systematic evaluation of this treatment with routine clinical populations. The current case report describes the assessment, formulation, and treatment of a patient with low self-esteem, depression, and anxiety symptoms. At the end of treatment (12 sessions over 6 months), and at 1-year follow-up, the treatment showed large effect sizes on measures of depression, anxiety, and self-esteem. The patient no longer met diagnostic criteria for any psychiatric disorder, and showed reliable and clinically significant change on all measures. As far as we are aware, there are no other published case studies of CBT for low self-esteem that report pre- and posttreatment evaluations, or follow-up data. Hence, this case provides an initial contribution to the evidence base for the efficacy of CBT for low self-esteem. However, further research is needed to confirm the efficacy of CBT for low self-esteem and to compare its efficacy and effectiveness to alternative treatments, including diagnosis-specific CBT protocols. © 2009.